2018
DOI: 10.1111/jsbm.12422
|View full text |Cite
|
Sign up to set email alerts
|

Does Family and Lone Founder Involvement Lead to Similar Indebtedness?

Abstract: This study evaluates whether the presence of a lone founder and family involvement impact private firms’ leverage differently from a methodological view. Using a sample of 4,102 private firms in Spain and taking under consideration a panel data structure from 2006 to 2013, we find that lone founder and family involvement matter in capital structure decisions and size shapes the forementioned influence. Our findings show that lone founder involvement always implies higher debt than the rest of firms and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 111 publications
(179 reference statements)
2
15
0
Order By: Relevance
“…Nevertheless, in this study, fixed-effect estimation is not appropriate given the time-invariant nature of both the moderating variable, i.e., family management, and certain control variables, such as territorial subdivisions and industries dummies [100]. Therefore, following prior research [101,102], it is more pertinent using random-effects models. According to the abovementioned specifications, different models based on the following equation are estimated: Sustainable economic performance = β 0 + β 1 Intramural R&D t-3 + β 2 Extramural R&D t-3 + β 3 Product innovation t-1 + β 4 Process innovation t-1 + β 5 Family involvement in management + β 6 Intramural R&D t-3 x Family involvement in management + β 7 Extramural R&D t-3 x Family involvement in management + β 8 Product innovation t-1 x Family involvement in management + β 9 Process innovation t-1 x Family involvement in management + β j x Controls + ε Table 2 shows the means, the standard deviations and the correlations of the variables under study.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, in this study, fixed-effect estimation is not appropriate given the time-invariant nature of both the moderating variable, i.e., family management, and certain control variables, such as territorial subdivisions and industries dummies [100]. Therefore, following prior research [101,102], it is more pertinent using random-effects models. According to the abovementioned specifications, different models based on the following equation are estimated: Sustainable economic performance = β 0 + β 1 Intramural R&D t-3 + β 2 Extramural R&D t-3 + β 3 Product innovation t-1 + β 4 Process innovation t-1 + β 5 Family involvement in management + β 6 Intramural R&D t-3 x Family involvement in management + β 7 Extramural R&D t-3 x Family involvement in management + β 8 Product innovation t-1 x Family involvement in management + β 9 Process innovation t-1 x Family involvement in management + β j x Controls + ε Table 2 shows the means, the standard deviations and the correlations of the variables under study.…”
Section: Methodsmentioning
confidence: 99%
“…According to the present literature review, researchers [3,39,49] identified two categories of debt financing: internal and external financial sources. According to Chua et al [50], and Hillier et al [51], new ventures of family firms are often debt financing through loaning, asset-liability, and debt-credit.…”
Section: Debt Financingmentioning
confidence: 99%
“…Then, the business was featured as a family firm when at least two people with the same surname were involved in the business as shareholders, CEO or board directors (Villalonga and Amit, 2006;Anderson and Reeb 2003;Garc ıa-Castro and Casasola, 2011). Previous studies (Arosa et al, 2010;Garcia-Castro and Casasola, 2011;L opez-Delgado and Di eguez-Soto, 2015;Di eguez-Soto and L opez-Delgado, 2019) that also used a sample with data extracted from SABI database, confirmed the suitability of the former criteria, i.e. the surname coincidence to identify family firms.…”
Section: Data and Variablesmentioning
confidence: 67%